An attempt to use color as a tool for high resolution correlations between estuarine sedimentary cores from Algarve (Portugal) - Mestre, Nélia (2013)
Nowadays, paleoenvironmental and climatological researches focus on studying shortterm climatic changes and one of the more sensitive environments for recording those short-term climatic variations are the high sedimentation rate of coastal regions. Accordingly, 4 estuaries from the Algarve region, south of Portugal, have been cored in order to study sedimentary and climatic variations during recent times (c.a. 5000 yrs). For this purpose, we applied sampling and analytical techniques from deep-sea studies, allowing the acquirement of almost continuous data profiles, as the color data obtained with the spectrophotometer Colortron.